Participatory action research in community development processes: an inter university cooperation in the Jesus María neighborhood in Cuba´s Old Havana - Noelia Melero Aguilar; Reina Fleitas Ruíz (Sociedad Iberoamericana de Pedagogía Social, 2015)
This paper presents part of an inter-university cooperation project which aims to create a process of awareness and community participation concerning the issue of water in the Jesus Maria neighborhood in the municipality of Cuba´s Old Havana. Based on a critical, emancipatory and transforming approach of reality we conducted participatory action research - which has several stages which develops different processes such as action-reflection, involving researchers, neighbors and neighborhood representatives, in the identification of access problems and water management, and in the preparation of proposals and improvement actions regarding this natural resource. On the one hand the research shows, the enormous potential of the territory in the production of knowledge, and linking it to social action, and secondly, the role of  universities in strengthening local community structures, from sharing  interdisciplinary knowledge and work methodologies that will enable us to obtain integral solutions according to the needs of its beneficiaries.